Pengaruh Current Ratio, Debt To Equity Ratio, Total Asset Turnover Dan Perputaran Kas Terhadap Profitabilitas Pada Perusahaan Industri Barang Konsumsi Yang Terdaftar Di Bei Tahun 2016-2019 - Fitri Sari Bina; Sarce Joti Natalia; Rika Marbun; Friska Darnawati Sitorus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study is to determine the effect of the current ratio, debt to equity ratio, total asset turnover, and cash turnover ratio on profitability in consumer goods industrial companies listed on the Indonesia Stock Exchange. -2019. The sample was determined by purposive criteria technique, obtained a sample of 31 companies. The type of data in this study is secondary data obtained from the financial statements of Infrequent Consumption Industry companies listed on the Indonesia Stock Exchange. With the results of the study showing that: Current Ratio (CR) does not affect and does not significantly affect ROA, Debt To Equity Ratio (DER) has a positive and significant effect on ROA, Total Asset Turn Over (TATO) has a positive and significant effect on ROA, Cash Turn Over does not affect and is not significant to ROA. Keywords: Curren Ratio, Debt To Equity Ratio, Total Asset Turn Over, Cash Turn Over